Effect of Embroidery Style on the Bandwidth of Textronic RFID UHF Transponder Antenna - Magdalena Nizioł; Piotr Jankowski-Mihułowicz; Mariusz Węglarski (Sensors)
The production of consumer electronics using electrically conductive materials is a dynamically developing sector of the economy. E-textiles (electronic textiles) are also used in radio frequency identification technology, mainly in the production of tag antennas. For economic reasons, it is important that the finished product is universal, although frequencies in radio systems have different values in different regions of the world. Therefore, the antenna bandwidth must be sufficiently wide so that the read range of the tag is maximally large for all frequencies of the specified band. The bandwidth of an antenna depends on its type and geometric dimensions, but this parameter can also be influenced by the way a given type of antenna is made. The authors prepared samples of embroidered RFID tag antennas for the UHF band using various types of embroidery. Then, its impedance and the read range of the tag were examined in order to determine the exact influence of the type of embroidery on the parameter of interest (antenna bandwidth). The results obtained during the research indicate the influence of different embroidery styles is present; however, that influence is not significant.